What matters now : how to win in a world of relentless change, ferocious competition, and unstoppable innovation - Hamel, Gary. (San Francisco, CA : Jossey-Bass, 2012)
'Critical insight from the man Fortune called'the world's leading expert on business strategy'About the only thing a leader can be sure of is that what worked yesterday is unlikely to work today, let alone tomorrow. Never before have businesses faced a more fractured, contentious and dynamic environment. If ever there was a need for fundamentally new thinking about values, competition, leadership, organization talent, and how these things are directly tied to management, it is now. Gary Hamel lays out an essential agenda in a world where old nostrums aren't merely useless, but downright toxic. Contains more than 25 standalone chapters in six sections that are brutally honest and tackle critical management and leadership challenges head-on Explains how to move from defense to offense, reverse the tide of commoditization, and outrun change Tackles how to effectively hack management, capture the moral high ground, and foster extraordinary contribution Written by one of the world's most prescient management experts and the acclaimed author of The Future of Management Concise and to the point, What Matters Now will inspire leaders to rethink their business, their management, and how they lead'--
Includes index.
Keywords: Management; Organizational change; Organizational effectiveness; Strategic planning